The role of inflammation in the development of acute gastroduodenal ulcer bleeding. - Sulaieva, O. N.; Barinov, E. F.; Kondratenko, P. G.; Zharikov, S. O.; Radenko, E. E. (Морфологія / Morphologia / Morfologìâ, 2014)
Background. Gastroduodenal ulcer bleeding is one of the main causes of morbidity, mortality and high medical care expenses. It is unclear why regardless of the optimization of antisecretory therapy among the patients with peptic ulcer the frequency of bleeding remains as high. Objective. We suggest that acute bleeding development is related with hyperstimulation of acute inflammatory response due to macrophages dysfunction. Methods. To test this hypothesis we assessed characteristics of inflammatory process in different zones of the gastroduodenal area under acute bleeding in 46 patients. The number and distribution of neutrophils, eosinophils, plasma cells, mast cells, macrophages (CD68+), T- (CD3+) and B-lymphocytes (CD20+) were evaluated. Results. The comparison of morphological changes in ulcer margin and intact gastric mucosa has revealed that the development of ulcer bleeding is associated with acute inflammation. High recruitment of neutrophils in ulcer margin was associated with edema and alteration of covering epithelium. CD68-positive cells prevailed in subepithelial region. However, in the 2nd group number of macrophages (p<0,001) and neutrophils was dramatically higher (p<0,01), that was accompanied with glands damage. CD68-positive cells were found not only under epithelium, but also close to gastric glands isthmus where epithelial stem cells are located, within disrupted muscularis mucosae and near lymphocytes infiltrates. Macrophage number correlated with neutrophils recruitment (r=0,696; p<0,01), intensity of edema and alteration of ulcer margin (r=0,741; p<0,001). Conclusion. Ulcerogenesis is related with alternative changes in immune reactivity. Acute ulcer bleeding is associated with progressive acute inflammation correlating with increase of macrophages number in ulcer margin and their proinflammatory activation.